The Proposed Amendment to the Definition of “Veldfire” as Articulated by The National Veld and Forest Fire Amendment Bill [B22–2016] - Glenwin Sefela (Obiter, 2020)
It goes without saying that fire is an important factor in the development of humankind. When humans first discovered fire, it instantly became their best friend. Fire enabled early humans to light up the dark, indulge in cooked meals and provide warmth for their bodies and homes. However, even before they figured out how to manually reproduce fire, it existed in nature. Fire, and specifically “veldfire”, exists naturally and does not need the agency of man. Today, severe drought, specific weather conditions (for example, high temperatures, high wind speed and low rainfall combine to induce favourable veldfire conditions) and an array of other factors (such as topography, land size, fuel type, population density (human influence) and climate change) all increase the possibility of a veldfire occurring. Owing to these contributing factors, fire has become both friend and, in some instances, deadly foe. For example, fire is used as a friendly management tool to prevent or lower the risk of veldfire, while an example of fire as foe are what are now commonly known as the “Knysna Fires” of 2017, which remain a vivid reminder of what uncontrolled fires can do. This type of fire not only damaged social, economic and environmental assets, it also quickly escalated into an emergency incident. An “incident” is defined in s 30(a) of the National Environmental Management Act 107 of 1998 to mean “an unexpected sudden occurrence, including a major emission, fire or explosion leading to serious danger to the public or potentially serious pollution of or detriment to the environment, whether immediate or delayed.” The Knysna Fires are a classic example of why managing veldfires in an integrated way is important within a South African context and are one of the main reasons for the promulgation of the National Veld and Forest Fire Act (101 of 1998) (NV&FFA) (s 3). Regrettably, however, the NV&FFA defines neither “veld” nor “veldfire”. Instead, it defines “fire” to “include a veldfire” and goes on inadequately to explain that “veldfire” means “veld, forest and mountain fire”. Taking the above reasoning into consideration, arguably one of the main challenges of the NV&FFA is the strict interpretation and inadequacy of the term “veldfire”. In refreshing contrast, however, the National Veld and Forest Fire Amendment Bill (the Bill) aims to provide more meaning to the term “veldfire”. The purpose of this note is therefore a critical analysis of the proposed amendment to the definition of veldfire by:  providing legislative background to the term “veldfire”;  investigating the way the courts of the past have interpreted the term legislative background and consequently “veldfire”;  explaining why the proposal to amend the term “veldfire” is important;  briefly looking at how other countries define their equivalent of South Africa’s “veldfire”; and, lastly,  by providing remarks and suggestions.